Body Image dalam Video Klip LOONA "Butterfly" - Affiyah Triyuni Sari; Cici Eka Iswahyuningtyas (LONTAR: Jurnal Ilmu Komunikasi, 2023)
Mass media builds the construction of women's body images. Women's beauty is judged by certain indicators, including slim bodies, fair skin, and straight hair. The unrealistic body image displayed by the mass media has a negative impact on the audience, especially female adolescents. Meanwhile, LOONA's â€œButterflyâ€ music video defy beauty standards. Adolescent fans tend to internalize the values â€‹â€‹that exist in the figure of the idol. This study aims to explain the reception of LOONA's teenage fans for aspects of body image in LOONA's "Butterfly" music video. The theory used in this study is reception analysis. This research was conducted qualitatively through in-depth interviews with female adolescent fans of LOONA. The results of the study show that the position of reception of LOONA's adolescent fans on aspects of body image in LOONA's "Butterfly" music video is dominated by a dominant position. The reception of LOONA's adolescent fans is influenced by the frameworks of knowledge, relations of production, and technical infrastructure.